Agrobacterium-mediated transformation of Carica papaya L. var ‘Eksotika’ with improved resistance to dieback disease - A. Razak, Roslinda (2017)
Papaya or Carica papaya L. is a tropical fruit that is popular worldwide. The Carica papaya L. var ‘Eksotika’ introduced by the Malaysian Agricultural Research and Development Institute (MARDI) in 1987, is a highly sought after cultivar grown in Malaysia. Unfortunately the Malaysian papaya industry in recent years has been afflicted by many diseases. One of the major diseases identified is the papaya dieback disease caused by the bacteria Erwinia mallotivora. This disease was first reported in Batu Pahat, Johor in 2003. The disease can affect the whole papaya plantation via soil, airborne and environmental conditions. Current method to address this disease is by demolishing the infected area. However, this method is ineffective because the infected area will be destroyed. Therefore, this project was aimed to combat the disease by genetically engineering a papaya dieback resistance gene into the papaya plant genome via Agrobacterium-mediated transformation. Throughout the years, development of transgenic plants frequently relies on antibiotic as a selectable marker, which raises public concern. Hence, in this study marker-free transgenic papaya plants were created via positive selection using the phosphomannose isomerase (pmi) gene. Phosphomannose isomerase (PMI) is an enzyme that converts mannose-6-phosphate to fructose-6-phosphate, a glycolysis intermediate that supports the growth of plant cells. To establish a marker-free positive selection system using this PMI, the effects of mannose on the growth and development of embryogenic ‘Eksotika’ papaya callus was evaluated. One-month old embryogenic calli were cultured on Murashige and Skoog (MS) medium in which 60 g/L sucrose in the original recipe was replaced with different concentrations of mannose and sucrose. Mannose was supplied as the sole carbon source or in combination with sucrose at 0, 5, 10, 15, 20, 25 or 30 g/L. Embryogenic calli cultured on medium supplemented with a ratio of 0:60 g/L mannose:sucrose was used as a control. The result after six sub-cultures showed that mannose at 30 g/L mannose was effective for screening transformed embryogenic calli. Evaluation of papaya transformation efficiency using this positive selection system was pursued using one-month-old embryogenic Agrobacterium-transformed calli harbouring pNOV2819 carrying the pmi gene. Only transformed cells were capable of utilizing mannose as a carbon source to grow. After five months on mannose selection,all 70 putative transformants obtained were PCR-positives for the pmi gene. Having established an antibiotic-free selection system, the next stage was targeted at combating the dieback disease. Plant disease caused by bacteria had been related to quorum sensing; whereby the bacteria monitors each other by secreting a small signal molecule known as autoinducer. It was hypothesized that interference of the signalling molecule of bacteria pathogen during infection could starve off infection. Hence, in this study, homoserine lactone (AHL)-lactonase gene isolated from Bacillus sp. strain 240B1 was used as a quorum quencher against the signalling molecule, AHL. To investigate the resistance of the ‘Eksotika’ papaya against Erwinia, the anti-pathogenic gene cassette constructed as pNOV2819:pmi:AHL-lactonase was transformed into the ‘Eksotika’ papaya embryogenic callus using Agrobacterium tumefaciens strain LBA4404. Mannose at 30 g/L was used during the selection process. Stable in vitro transgenic papaya plants were successfully obtained within 7 to 8 months on De Fossard medium during regeneration. A total of 154 transgenic plants harbouring pmi and AHL-lactonase were obtained out of 1740 transformed calli. The overall transformation frequency of pNOV2819:pmi was 10.8 % and pNOV2819:pmi:AHL-lactonase was 8.1%. PCR analysis verified to confirm that the transgene was successfully integrated into the T0 ‘Eksotika’ papaya plants and the transgene was not detected in the control. In order to assess the level of resistance of T0 plants produced against dieback, T0 plants aged 5 to 6 months were injected with a needle at the stem area by bacteria Erwinia mallotivora. The result showed the control plant began to experience dieback symptoms as early as 3 days after infection. The symptoms then spread and infected other plant parts. While for transgenic plant lines, the shoots wilted and fortunately the symptoms did not spread to the other parts of the plant. The results of screening between this pathogen and AHL-lactonase proved that the transformation successfully disrupted the communication of the pathogen and able to reduce the spread of bacteria.